Modified itu-r rain attenuation prediction model for a tropical station - Yussuff, Abayomi Isiaka (2013)
Most satellite communication takes place above the 10 GHz frequency bands, a direct consequence of over-congestion of lower frequency bands. A dearth of database along the slant path in the tropical regions for use in rain propagation studies at microwave frequencies, made further studies at millimeter wave band quite attractive. Rain height data were sourced from the Tropical Rainfall Measuring Mission (TRMM) 3B43 V6 and NigComSat-1 satellite for 37 stations in Nigeria as reported in the literature. Terrestrial attenuation measurement data at 0.01% of time, sourced from the Universiti Teknologi Malaysia’s Wireless Communication Centre (WCC) were transformed to slant path attenuation values using a transformation technique. Attenuation exceeded for other percentages of time were obtained using statistical methods. The ITU-R model is modified to suit the results. Further analysis at 12 GHz suggested that the proposed modified ITU-R model show good performance when compared with other models of interest.